Do labor market regulations affect the link between innovation and employment? Evidence from Latin America - Laura Baensch; Maria Laura Lanzalot; Giulia Lotti; Rodolfo Stucchi (Inter-American Development Bank (IDB), 2018)
The link between innovation and employment is at the center of the policy debate. This paper sheds light on how labor market regulations affect the relationship between different types of innovation and employment in Latin America. We estimate the model developed by Harrison et al. (2014) using Enterprise Surveys for 14 Latin American countries. We find that: (i) product innovations have a positive impact on employment growth; (ii) process innovations do not affect employment growth; (iii) more rigid labor market regulations (minimum wages and severance payments) reduce the effects of innovation.
Keywords: D2; J21; J38; L60; O31; 330; Process Innovation; Product Innovation; Employment Growth; Labor Markets Regulations; Latin America